PENGARUH MODEL GROUP INVESTIGATION TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR ARTIKEL PENELITIAN OLEH: FITRI SELIA SUMARDHA NIM F1081151065 PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR JURUSAN PENDIDIKAN DASAR FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS TANJUNGPURA PONTIANAK 2019 PENGARUH MODEL GROUP INVESTIGATION TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Sumardha, Fitri Selia; Sugiyono, Sugiyono; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed was to describe the influence model of Group Investigation of student learning output in learning Social studies in grade V of State Elementary School 06 North Pontianak. the research method was an experiment, form of quasi Experimental's non-equivalent group design. the research population of all grade V students of public Elementary School 06 North PontianakÂ  werw counted to 43 students. the withdrawal sample technique used saturation sampling. the technique used was observation and measuring. the data collection tools are observation sheets and multiple choice tests. the data result was the average score of class control post-test was 70,82 and the experiment was 78,67. based on the counting result t-test was 2,370 > t-table 2,020 then ha is accepted. it shows that there is a difference in students learning output of class control and class experiment. the value of effect size was 0,76 with middle criteria. it can conclusion that there is an effect of the application of the Group Investigation model on student learning output in learning Social studies in grade V public Elementary School 06 North Pontianak.Â Keywords: Influence, Group Investigation Model, Learning Outcomes, Social Studies Learning